Miths and solutions in digital dental impression - Guilherme Cabral; Luciana M Soares; Hilton Riquieri; Adriano Baldotto Barbosa; Renato Sartori; Eric Padovani; Fabio Costa; Jonas U.R. Schindler; Juliano Arantes Vasconcelos; Diego Henrique de Lima (Journal of Dental Problems and Solutions - Peertechz Publications, 2022)
Nowadays, the process of transferring intra-oral information from the dental office to dental laboratories has been a current reality in dentistry. The number of advantages presented in this process include work accuracy, patient acceptance, a transfer, and storage information facility, three-dimensional visualization, and an increase in time efficiency [1].